Peran Kepolisian Terhadap Ancaman Kejahatan Pelecehan Seksual melalui Modus Deepfake Porn di Era Digital - Naufal Zuhdi; Heni Siswanto; Dona Raisa Monica (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The advancement of artificial intelligence (AI) has led to the emergence of new crimes, including the misuse of deepfake technology to produce and distribute pornographic content without the victim's consent. This form of digital sexual harassment has serious impacts on victims' dignity, mental health, and social life. This study aims to examine the efforts of Police in addressing sexual harassment crimes using deepfake porn and to identify the obstacles faced. Using normative and empirical legal approaches, data were collected through literature review and interviews. The findings reveal that the police efforts involve both penal (law enforcement) and non-penal (preventive) approaches, including public education, cross-institutional collaboration, and cyber patrols. However, the handling of such crimes is still hindered by regulatory gaps, limited technology, and low public awareness. Strengthening legal frameworks and police capacity is essential to effectively combat digital-based sexual crimes.